Faith Church: Roma Baptists Challenging Religious Barriers in Interwar Romania - Ploscariu, Iemima (2020)
In interwar Romania, the numbers of Baptists grew exponentially among the ethnic majority population in the border regions of Transylvania, Banat, and Bessarabia. In the competition over souls and for cultural space in the newly formed Greater Romania, the Roma became an important minority to win over. In 1930, Petar Mincov visited Chișinău and spurred outreach to the Roma among Romanian Baptists as he had in Bulgaria. It was here and in the cities of Arad and Alba-Iulia that some of the first Romanian Roma converted to the Baptist denomination. The first Roma Baptist (and first Roma neo-Protestant) Church, called Biserica Credinţa (Faith Church), was founded in Arad city around 1931. Confessional newspapers in English, Romanian, and Russian from the interwar period reveal the initiative taken by members of the local Roma community to convert and to start their own church. The article analyses the role of Romanian Baptist leadership in supporting Roma churches and the development of these new faith communities in the borderland regions. Unlike outsider attempts to foster a Roma Baptist community in Bucharest, the Faith Church survived World War II and communist governments, and provides insight into the workings and agency of a marginalized double minority. The article also looks at the current situation of Roma evangelicals in Arad city and how the change in religious affiliation has helped or hindered attempts at inclusion and policy change.